2019
DOI: 10.1109/access.2019.2934979
|View full text |Cite
|
Sign up to set email alerts
|

Design of Traffic Emergency Response System Based on Internet of Things and Data Mining in Emergencies

Abstract: Urban emergencies are hard to avoid. Traffic emergency response after an incident plays an important role in reducing losses and is a key link in urban emergency management. However, the traditional traffic management methods have been difficult to face the complicated conditions and requirements in such problems. The introduction of Internet of Things and data mining technology to establish a traffic emergency response system under urban emergencies can significantly improve the level of urban emergency respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…Although public health emergency management has been paid much attention, the research in this area is still in its infancy and initial stage. Especially in the "top down" emergency response system, how to highlight the role and function of primary medical units is a problem that we are waiting to study at present, especially the remote public health emergency management of the Internet of things is also in the exploratory stage [27][28][29]. is paper will focus on the current situation and focus on analyzing the low delay emergency management system of remote public medical care based on the Internet of things, which has a strong convincing and promoting role in improving the relevant mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Although public health emergency management has been paid much attention, the research in this area is still in its infancy and initial stage. Especially in the "top down" emergency response system, how to highlight the role and function of primary medical units is a problem that we are waiting to study at present, especially the remote public health emergency management of the Internet of things is also in the exploratory stage [27][28][29]. is paper will focus on the current situation and focus on analyzing the low delay emergency management system of remote public medical care based on the Internet of things, which has a strong convincing and promoting role in improving the relevant mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al ( 2018 ), Xu et al ( 2018 ) To design a traffic emergency response system based on Internet of Things to improve the level of emergency response. Liu and Wang ( 2019 ) To analyse how IoT (in confluence with other technologies) has the potential to revamp the healthcare system, in order to cope with the burden of modern diseases and the challenge of scaling up to ever-increasing populations. Latif et al ( 2017 ) To propose a IoT based solution using the task-technology fit approach for an effective and efficient disaster management.…”
Section: Resultsmentioning
confidence: 99%
“…method is analyzed from the aspects of model definition, model training, and decoding algorithm. In view of the specific language scenarios where the ethnic corpus is insufficient, the phrase extraction method that ignores the non-contiguity of position in traditional phrase extraction is improved, the strategy of extracting and decoding non-contiguous phrases is realized, the small-scale corpus is fully utilized [30]; then, the experimental comparison between the traditional algorithm and the extraction model algorithm of non-contiguous phrases is carried out. The experimental results have shown that the comparison between the proposed algorithm and the traditional algorithm is improved, which means that the proposed model algorithm for extracting non-contiguous phrases is more effective than the traditional model for extracting contiguous phrases in M.T.…”
Section: Discussionmentioning
confidence: 99%